Metabolic syndrome as a growing problem of population in clinical and epidemiological perspectives - Rutowski, J.A. (Актуальні проблеми транспортної медицини, 2012)
Metabolic syndrome is a conglomeration of factors that contribute to the development of atherosclerotic plaque. As of obesity, which is one of the diagnostic criteria of metabolic syndrome by hypertension and atherogenic dyslipidemia all these elements contribute to the development of atherosclerosis. It is commonly believed that the development of metabolic syndrome are responsible genetic predisposition and environmental factors, which consist of such calories and atherogenic diet and low physical activity. The prevalence of metabolic syndrome in populations is diverse in terms of ethnicity, age and gender. It is characterized by obesity, hypertension, type 2 diabetes, insulin resistance and lipid disorders. Effects and risks of particular types of diseases and disorders are mutually enhancing and adding up, which increases risk of adverse complications. According to World Health Organization (WHO) data in the 6 billion people in the world, 175 million have diabetes, and expects that over the next 25 years this number will increase to 250 million. Despite therapeutic advances, diabetes is not to cure disease that causes disability and shortens the average duration of life of patients by 20-30%. It is estimated that the treatment of diabetes and its complications consumes about 7% of all material expenditures on health
care in Poland. In the United States of America, over 65% of people suffer from obesity, in Europe, this problem affects more than 67% of the population. It is estimated that in Poland about 20% or more of adults are obese. European Group for the Study of Insulin resistance (EGIR), based on WHO criteria, in several populations of different European countries assessed the occurrence of this syndrome in persons aged 40 - 55 years 7 - 36% in men
and 5 - 22% in women. Data on the prevalence of metabolic syndrome in Poland was obtained from the study and obtained in corresponding WOBASZ study. In both studies the prevalence of metabolic syndrome was assessed NCEP - ATP III in 2001 and the most recent version of 2005. Based on these data, it appears that metabolic syndrome occurs on average every fifth of an adult, almost 6 million Polish citizens. Метаболический синдром представляет собой ряд факторов, которые способствуют развитию атеросклеротических бляшек. Ожирение, которое является одним из диагностических критериев метаболического синдрома, артериальная гипертензия и атерогенные дислипидемии способствуют развитию атеросклероза. Считается, что за развитие метаболического синдрома отвечают генетическая предрасположенность и факторы окружающей среды: высокалорийная и атерогенная диета на фоне низкой физической активности. Распространенность метаболического синдрома в популяции зависит от этнической принадлежности, возраста и пола. Он характеризуется ожирением,
артериальной гипертензией, сахарным диабетом 2 типа, инсулинорезистентностью и нарушением липидного обмена.Суммация и потенцирование эффектов и рисков отдельных видов заболеваний и расстройств увеличивают риск побочных осложнений. По данным Всемирной организации здравоохранения (ВОЗ) из 6 миллиардов человек в мире, 175 миллионов человек больны диабетом, и ожидается, что в течение последующих 25 лет их число увеличится до 250 миллионов. Несмотря на терапевтические достижения в терапии диабета, он вызывает инвалидность и сокращает среднюю продолжительность жизни пациентов на 20-30%. Считается, что на лечение сахарного диабета и его осложнений расходуется около 7% всех материальных затрат на здравоохранение в Польше. В Соединенных Штатах Америки более 65% людей страдают от ожирения, в Европе эта проблема затрагивает более 67% населения.Считается, что в Польше более 20% взрослых страдают ожирением. Европейская группа по изучению инсулинорезистентности (Egir), по критериям ВОЗ, в популяциях различных европейских стран
оценивает возникновение этого синдрома у лиц в возрасте 40 - 55 лет 7 – 36 % у мужчин и 5 - 22% у женщин. Данные о распространенности метаболического синдрома в Польше были получены в собственных исследованиях и соответствующем исследовании WOBASZ. В обоих исследованиях распространенность метаболического синдрома оценивали по версии NCEP - ATP III в 2001 и 2005 годах. Из этих данных следует, что метаболический синдром возникает в среднем у каждого пятого взрослого, т.е. почти у 6 миллионов польских граждан. Метаболічний синдром являє собою ряд факторів, які сприяють розвитку атеросклеротичних бляшок. Ожиріння, яке є одним з діагностичних критеріїв метаболічного синдрому, артеріальна гіпертензія і атерогенна дисліпідемія сприяють розвитку атеросклерозу. Вважається, що за розвиток метаболічного синдрому відповідають генетична схильність і фактори навколишнього середовища: високалорійная і атерогенная дієта на тлі низької фізичної активності. Поширеність метаболічного синдрому у популяції залежить від етнічної приналежності, віку і статі. Він характеризується ожирінням, артеріальною гіпертензією, цукровим діабетом 2 типу,
інсулінорезистентністю та порушенням ліпідного обміну. Сумація і потенціювання ефектів і ризиків окремих видів захворювань і розладів збільшують ризик побічних ускладнень. За даними Всесвітньої організації охорони здоров’я (ВООЗ) з 6 мільярдів чоловік у світі, 175 мільйонів чоловік хворі на діабет, і очікується, що протягом наступних 25 років їх число збільшиться до 250 мільйонів. Незважаючи на терапевтичні досягнення в терапії діабету, він викликає інвалідність і скорочує середню тривалість життя пацієнтів на
20-30%. Вважається, що на лікування цукрового діабету та його ускладнень витрачається близько 7% всіх матеріальних витрат на охорону здоров’я в Польщі. У Сполучених Штатах Америки більше 65% людей страждають ожирінням, в Європі ця проблема зачіпає більше 67% населення.Вважається, що в Польщі більше 20% дорослих страждають ожирінням. Європейська група з вивчення інсулінорезистентності (Egir) за критеріями ВООЗ, в популяціях різних європейських країн оцінює виникнення цього синдрому у осіб
віком 40 -55 років 7 -36% у чоловіків і 5-22% у жінок. Дані про поширеність метаболічного синдрому у Польщі були отримані у власних дослідах та дослідженні WOBASZ. В обох дослідженнях поширеність метаболічного синдрому оцінювали за версією NCEP -ATP III в 2001 і 2005 роках. З цих даних випливає, що метаболічний синдром виникає в середньому у кожного п’ятого дорослого, тобто майже
у 6 мільйонів польських громадян.